Forced drainage water management technology in Côte d’Ivoire - CGIAR Research Program on Rice (2019)
The effect of forced drainage compared to the reference method of water management – continuous flooding – on methane, nitrous oxide and rice yield is being evaluated in the research station of Mbe, Cote d’Ivoire. Preliminary results will be available by the end of 2020.